Adverse childhood experiences and disengagement from HIV care: a case-cohort study in Tanzania - Sydney Tucker; Solis Winters; Emmanuel Katabaro; Matilda Mlowe; Patrick Bradshaw; Jennifer Ahern; John Colford; Laura Packel; Susan Hillis; Amon Sabasaba; Prosper Njau; Sandra I. McCoy (AIDS Research and Therapy)
Abstract Adverse childhood experiences (ACEs) can have lasting, detrimental effects throughout the lifespan and may influence engagement in health care. We conducted a case-cohort study in Tanzania to estimate the association between ACEs and disengagement from HIV care 12 months after initiating antiretroviral therapy (ART) among 217 adults (26 cases and 191 sub-cohort participants). Experiencing one, two, three, and four additional ACEs was significantly associated with 28% (RRa= 1.24; 95% CI: 1.05, 1.44; p-value < 0.01), 64% (RRa=1.64; 95% CI: 1.22, 2.20), 110% (RRa=2.10; 95% CI: 1.35, 3.26), and 168% (RRa=2.68; 95% CI: 1.49, 4.38) increases in the risk of disengagement from HIV care, respectively. These findings call for integrated trauma-informed mental health services within HIV care to end HIV/AIDS as a public health threat.